The Effect Of Using Project Based Learning Method On Students’ Reading Comprehension At The Eighth Grade Students of SMPS IT IDBS Pinggir - Dini Deswarni; Laili Fauziah (Jolly Journal of English Education, 2025)
This research was carried out to find out The Effect of Using Project Based Learning Method Toward Students' Reading Comprehension at the Eighth Grade of SMPS IT IDBS Pinggir. The population consisted of 102 eighth-grade students, and 51 students were selected as samples through cluster sampling. Class VIII Sabar (25 participants) was assigned as the experimental group, and class VIII Jujur (26 participants) as the control group. This research used a quasi-experimental method with pre-test and post-test design. The instrument was a multiple-choice reading comprehension test based on indicators of narrative text understanding. The results showed a significant improvement in students’ reading comprehension taught using the Project Based Learning method. The average post-test score of the experimental group was 78.60, while the control group scored 60.46. The Independent Sample T-Test result showed a significance value (Sig. 2-tailed) of 0.001<0.05, indicating that the null hypothesis was rejected. Thus, it can be concluded that the Project Based Learning method significantly improves students’ reading comprehension at the eighth grade of SMPS IT IDBS Pinggir.